Interaksi Teman Sebaya Dan Perkembangannya Dalam Pembentukan Perilaku Sosial Anak Sekolah Dasar - Ridwan Ardi (Prodi PGSD Unsultra, 2025)
Elementary school children's social behavior develops along with their interactions with peers. These interactions play an important role in the formation of values, norms, and social skills that will affect children's social lives in the future. This literature study aims to analyze how peer interactions contribute to the development of elementary school children's social behavior. This study uses a literature review method by analyzing various previous studies that discuss this topic. The results of the study indicate that interactions with peers help children understand social norms, develop empathy, and improve communication and cooperation skills. Factors such as parenting patterns, school environment, and culture also influence the formation of children's social behavior. Thus, it is important for teachers and parents to provide appropriate guidance in supporting positive social interactions among children.